Evaluating the association between dairy consumption, acne development and quality of life among university students - Shariman, Adrina Munirah; Azahari, Nuraniza; Mohamed Nor, Noraishah; Afandi, Aflah (IIUM Press, 2025)
Background: Acne vulgaris is one of the most prevalent dermatological conditions among adolescents and young adults, often impairing self-esteem, social relationships, and quality of life. Dietary factors, particularly dairy intake, have been suggested to contribute to acne, although findings remain inconsistent. This study aimed to evaluate the association between dairy consumption, acne severity, and quality of life among the students of the International Islamic University Malaysia (IIUM). Methods: A cross-sectional study was conducted among 377 undergraduate students from three IIUM campuses. Data were collected using a self-administered questionnaire comprising a modified Food Frequency Questionnaire (FFQ) for dairy intake, the Global Acne Grading System (GAGS) for acne severity, and the Acne-Specific Quality of Life (Acne-QoL) questionnaire. Spearman’s rank correlation was performed to determine associations between variables. Results: The mean daily dairy intake among students was 470.68 ± 183.88 g/day. Yoghurt and fresh milk were the most consumed dairy products. No significant association was found between overall dairy intake, fresh milk, yoghurt, or cheese with acne severity. However, commercial milk, powdered milk, and evaporated milk showed a significant positive correlation with acne severity (p < 0.005). Regarding quality of life, acne severity was negatively correlated with all four Acne-QoL domains (self-perception, role-social, role-emotional, and acne symptoms), with the strongest correlation observed in the acne symptoms domain. Conclusion: This study suggests that certain forms of dairy, particularly commercial, powdered, and evaporated milk, may contribute to acne severity among university students. Acne was also found to adversely affect multiple domains of quality of life. These findings highlight the importance of dietary counselling and holistic acne management strategies for young adults. Further research considering additional lifestyle and genetic factors is warranted.